Factors Influencing Teachers’ Use of Multimedia Enhanced Content in Secondary Schools in Tanzania - Mtebe, Joel Samson; Mbwilo, Betty; Kissaka, Mussa M. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
Tanzania is faced with a severe shortage of qualified in-service school science and mathematics teachers. While science and mathematics account for 46% of the curriculum, only 28% of teachers are qualified to teach these subjects. In order to overcome this challenge, the Ministry of Education and Vocational Training (MoEVT) implemented a project to use multimedia-enhanced content to upgrade subject content knowledge of science and mathematics teachers in secondary schools. A total of 70 topics and 147 subtopics were developed and enhanced with various multimedia elements. The content was used to train 2,000 in-service science and mathematics teachers from secondary schools in 19 selected centers countrywide. However, the presence and availability of this content does not automatically guarantee that teachers will use them. For this content to improve teachers’ subject content knowledge, they must be accepted and used by teachers in secondary schools. This study examines factors affecting teachers’ acceptance and prolonged use of developed multimedia-enhanced content using the extended Unified Theory of Acceptance and Use of Technology (UTAUT2) as a research framework. A sample of 1,137 teachers out of 2,000 was collected and tested against the research model using regression analysis. With exception of performance expectancy, all other factors had a statistically significant effect on teachers’ acceptance and use of the developed content. The government and other stakeholders can use these findings to develop strategies that will promote acceptance and use of the developed content in secondary schools in Tanzania.